Harnessing the power of novel ruthenium-MOF for efficient wastewater treatment - Altharawi, Ali; Aldakhil, Taibah; Alossaimi, Manal A.; Afzal, Obaid (Frontiers in Materials, 2025)
A novel metal-organic framework (MOF) was synthesized using 4,4'-(diazene-1,2-diyl)dibenzoic acid and ruthenium (III) chloride via microwave-assisted synthesis. The resulting ruthenium-MOF exhibited a high specific surface area (1856 m2/g), and the inclusion of ruthenium, known for its biological activity, endowed the structure with potent antimicrobial properties against key wastewater bacterial strains. Furthermore, its abundant hydrogen bonding sites enhanced its adsorption capacity for phenol red, a major waterborne pollutant. The synthesized MOF demonstrated superior antimicrobial activity compared to certain commercial antibiotics. In adsorption experiments, 0.06 g/L of the MOF successfully removed 92% of 0.6 mg/L phenol red at pH 7 within 75 min, highlighting its rapid and efficient pollutant removal capability. These dual functions, antimicrobial and adsorptive, emphasize the potential of this ruthenium-MOF for practical environmental remediation and wastewater treatment applications.